Signed, sealed, delivered: using community-based social marketing to advance Extension communication services units in Kansas - Zagonel, Anissa M. (Kansas State University, 2019)
The purpose of this study was to enhance the K-State Research and Extension brand through community-based social marketing strategies that emphasize internal branding and sharing Extension's story. This purpose was achieved through the research objectives, hypothesis, and research question, which identified needs, barriers, and perceptions of two Extension communication services units from potential and current customers at Kansas State University. As an effect, this study provided strategic recommendations for services and clients. The research objectives, hypothesis, and research question were fulfilled through an online survey of KSRE teaching and research faculty, KSRE state specialists, KSRE county and district Extension agents, and KSRE office professionals. Previous research assessing the marketing of the two communication services units, University Printing and the KSRE Bookstore and Mail Center, has identified a confusion among employees’ understanding of current marketing strategies in place, policies about how and to whom products and services can be directed toward, and each of the entities’ and employees’ role in the bigger mission of Extension. In addition, these communication services units hold a unique relationship with customers in a cooperative purchasing agreement, which is commonly referred to as procurement contracts or approved vendors in many university settings. For this study, community-based social marketing was used as a theoretical framework because of the limited and decreasing budget for marketing, recommended use of self-proclaimed brand ambassadors, and the specialized campus and Extension community customer base. From the findings of this research, increasing familiarity of Extension communications services units’ services was selected as the CBSM end-state behavior. This study found a respondent need for service center information through email marketing (M = 3.88, SD = 1.28), online resources (M = 3.82, SD = 1.16; M = 2.80, SD = 1.34) and direct, personal contacts (M = 2.51, SD = 1.34), which was assessed on a five-point scale. Furthermore, there was a weak negative relationship, r = -.31, p = ≤ .000, between the perception of the service centers and those who felt restricted in purchasing options. Finally, respondents’ perceptions of the importance of each service center in sharing the story of Extension was found, which was M = 3.34, SD = 1.33 for University Printing and M = 3.66, SD = 1.26 for the K-State Research and Extension Bookstore and Mail Center on a five-point scale. Write-in answers regarding the service centers’ role in sharing Extension’s story provided more understanding and context to this research objective. In the linear regression model for RO3, the dependent variable was experiences that influence customers’ use of University Printing and the K-State Research and Extension Bookstore and Mail Center. The significant predictors were the K-State Research and Extension Bookstore and Mail Center’s importance variable, an adjusted perception variable, a familiarity of University Printing variable, a cooperative purchasing variable, and the service centers’ role in sharing Extension’s story variable. In the linear regression model for RO4, the dependent variable was the service centers’ role in sharing Extension’s story. The significant predictors were an adjusted experiences that influence customers’ use of University Printing and the K-State Research and Extension Bookstore and Mail Center variable, the K-State Research and Extension Bookstore and Mail Center’s importance variable, a familiarity of the K-State Research and Extension Bookstore and Mail Center variable, and a cooperative purchasing variable. The predictors from these models informed the CBSM strategies selected and described in recommendations. Specific CBSM strategies recommended in this study were changing social norms, using social diffusion, using prompts, increasing communication, and clarifying incentives. Within these strategies, recommended themes of messages included general familiarity, acknowledging cooperative purchasing, clarifying incentives, and utilizing the respondent-identified role of the service centers in sharing Extension’s story. By implementing the recommended strategies, both communication services units could increase use of services, familiarity among customers, and enhance the KSRE brand. Future assessment of these units and other similar structures could provide improvement data, as well as a more robust picture of the KSRE organization.
Keywords: Community-based social marketing; Extension communication services; Internal branding; Storytelling; Cooperative purchasing